Evolution of Social Security in the Lap of Public Action: Recounting the Experience of Kerala - K\P, Kannan and Pillai N., Vijayamohanan (MPRA Paper No. 9691, 2007)
This paper is part of a large study on the Social Protection in Rural India and China. In this paper, we attempt at a critical appraisal of the historical development and experience of social security initiatives in Kerala, India. We situate the development experience of Kerala in a conceptual framework of participatory development, which we interpret in a broad context of organization and mobilization of people at specific junctures of historical progress of a society. Thus participatory development, in our view is participation in the progressive process of realization of human rights and thus indevelopment; that is, public action, with an effective public demand and a wiling public supply, conditioned by the legitimate function of the state. It is also attempted to categorize the on-going social security schemes according to the definitional framework of our study, that is, in terms of the definitional division of social security into basic and contingent social security